Computed tomographic findings of trichuriasis - Tokmak, Naime (Baishideng Publishing Group Co., Limited, 2006)
In this report, we present computed tomographic findings of colonic trichuriasis. The patient was a 75-year-old man who complained of abdominal pain, and weight loss. Diagnosis was achieved by colonoscopic biopsy. Abdominal computed tomography showed irregular and nodular thickening of the wall of the cecum and ascending colon. Although these findings are nonspecific, they may be one of the findings of trichuriasis. These findings, confirmed by pathologic analysis of the biopsied tissue and Kato-Katz parasitological stool flotation technique, revealed adult Trichuris. To our knowledge, this is the first report of colonic trichuriasis indicated by computed tomography.